MÍDIA CRISTÃ E DITADURA CIVIL-MILITAR: MEMÓRIAS SILENCIADAS NO JORNAL EXPOSITOR CRISTÃO DA IGREJA METODISTA - RAMIRO, Marcelo Moreira (2017)
The objective of the present essay is to investigate how the newspaper Expositor Cristão approached, politically and ideologically during the civil-military dictatorship years, cases of violation of human rights against the Methodists. As such, this study aims at identifying and looking into precursory influences of silenced memories in the light of new revelations about the facts of that time, which were made possible in particular by the National Truth Commission. The theoretical reference seeks interaction between studies on Brazilian Protestantism and local Christian media to what concerns memory, silencing and how structures of feeling are built, making use of contributions from cultural studies. The methodological path to the objective is based on bibliographical and documentary research, besides the Discourse Analysis by the French School. This paper uses as the analysis core 146 issues of the referred newspaper published between 1968 and 1974, focusing on what was said or left implicit about the Theology College of the Methodist Church closed down in 1968, constraints on church members who were sent to prison, tortured, disappeared or killed, and ultimately the dawning of the democratic era brought in by the protestant president Ernesto Geisel in 1974. The research evidenced that the approach of protestant publications, particularly the Expositor Cristão, was in favor of the military government. Moved by the sentiment of anticommunism and religious moralistic ethics, there was support and assistance from leaders of the Methodist Church and their own newspaper so that crimes could be committed throughout the dictatorship years